2015
DOI: 10.1039/c5ra06810j
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic nano-Fe3O4@TiO2/Cu2O core–shell composite: an efficient novel catalyst for the regioselective synthesis of 1,2,3-triazoles using a click reaction

Abstract: An efficient and recoverable core–shell nanomagnetic composite was developed for regioselective synthesis of 1,2,3-triazoles using a green procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 77 publications
(26 citation statements)
references
References 65 publications
0
26
0
Order By: Relevance
“…It is worth mentioning that the results showed alkyl and aryl halides react better than haloketones in terms of yields and reaction times. The efficiency of CuI@[PMMA‐co‐MI] in click reaction was also compared with that of previously reported catalysts under various reaction conditions (Table ) . By comparison, it can be concluded that CuI@[PMMA‐co‐MI] as a novel nanocatalyst has several merits such as higher or comparable yield of the desired product in shorter reaction time.…”
Section: Resultsmentioning
confidence: 95%
“…It is worth mentioning that the results showed alkyl and aryl halides react better than haloketones in terms of yields and reaction times. The efficiency of CuI@[PMMA‐co‐MI] in click reaction was also compared with that of previously reported catalysts under various reaction conditions (Table ) . By comparison, it can be concluded that CuI@[PMMA‐co‐MI] as a novel nanocatalyst has several merits such as higher or comparable yield of the desired product in shorter reaction time.…”
Section: Resultsmentioning
confidence: 95%
“…A solution containing FeCl 3 .6H 2 O (1.35 g, 5 mmol), NaOAc.3H 2 O (3.85 g, 12.6 mmol), and 25 mL EG was added to the mixture, the mixture was stirred vigorously for 15 min, and it was transferred to a 100‐mL Teflon‐lined stainless steel autoclave and heated at 200 °C for 12 h. The black product was collected and washed with ethanol and deionized water several times, and finally dried at 80 °C in an oven overnight. By directly coating H‐Fe 3 O 4 with a layer of TiO 2 through hydrolyzing TBOT in ethanol and acetonitrile solution, H‐Fe 3 O 4 @TiO 2 spheres were synthesized . Fifty milligrams of the as‐synthesized H‐Fe 3 O 4 was dispersed in a mixed solvent containing 90 mL of ethanol and 30 mL of acetonitrile ultrasonically.…”
Section: Methodsmentioning
confidence: 99%
“…By directly coating H-Fe 3 O 4 with a layer of TiO 2 through hydrolyzing TBOT in ethanol and acetonitrile solution, H-Fe 3 O 4 @TiO 2 spheres were synthesized. [27] Fifty milligrams of the as-synthesized H-Fe 3 O 4 was dispersed in a mixed solvent containing 90 mL of ethanol and 30 mL of acetonitrile ultrasonically. Then, 0.5 mL of NH 3 .H 2 O was added to the mixture.…”
Section: Synthesis Of H-fe 3 O 4 @Tiomentioning
confidence: 99%
See 1 more Smart Citation
“…[28] Additionally, it brings important advantages such as eliminates the formation of byproducts (bistriazoles and diacetylenes), removal of the catalyst from the reaction media which can be achieved by simple filtration and, especially minimize the effective metal loading for reaction (recyclability and reusability). Recently, different heterogeneous supports [29][30][31][32][33][34][35][36] such as zeolites, montmorillonite, [37] chitosan, [38,39] graphene oxide, [31,40] cellulose [33,41] have been used for immobilization of copper, but these methods have some deficiencies such as long reaction time, use of organic solvents, high temperature, tedious work-up procedure, low yield, high catalyst loading so it is worthwhile to develop a new, convenient, widely applicable, green, sustainable, feasible and regio-controlled synthetic methodology for the facile preparation of fluorescent biologically important 1,2,3-triazoles.…”
Section: Introductionmentioning
confidence: 99%